EXPANSION OF NUMBERS (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
The topic of expansion of numbers (or mathematical expansions)involves representing numbers in various forms and studying their interrelationships. This field is especially relevant in mathematical analysis and algebra. The study of number expansions primarily focuses on their fractional, rational, or decimal representations and exploring their logical and analytical properties. Key concepts in number expansions include decimal expansions, fractional expansions, and periodic expansions. Decimal expansions are particularly important for calculating precise values in the real number system.Fractional expansions, on the other hand, help explore the properties of numbers expressed in specific forms.